Begining open heart surgery in Nepal: Our experience and three years audit at Tribhuvan University Teaching Hospital - Shrestha, Bishow ManSingh; Koirala, Bhagwan; Joshi, Purna Raj; Marahatta, Mod Nath; Bhatta, Mahendra; Timila, Rabindra; Timila, Rabindra; Shrestha, Uttam; Sharma, Joytendra; Lakhey, Paleswan; Pradhan, Sidhartha; Sharma, Govinda Prasad (Nepalese Heart Journal, 2000)
The historic first open heart surgery by the all-Nepalese team was performed at Tribhuvan University Teaching Hospital (TUTH) on 20 February 1997. Since then with-in three years period 132 cases of Open Heart Surgeries were performed. Retrospective study of those cases and problems faced in continuing the service is presented here.